5. FACTORS RELATED TO FUNGAL INFECTIONS IN ELDERLY PATIENTS TREATED AT TRA VINH GENERAL HOSPITAL FROM 2022 TO 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: The objective of this study was to identify factors associated with fungal infections in elderly patients presenting with with urinary tract infections or dermatitis at Tra Vinh General Hospital.Method: A descriptive cross-sectional study was conducted from 11/2022 to 6/2023. The study participants were all geriatric inpatients aged 60 years or older who had symptoms of urinary tract infections or dermatitis at Tra Vinh General Hospital.Results: The study indicated that fungal infection rates were associated with medical history factors such as kidney failure (p = 0.001, PR = 2.37, 95% CI: 1.45–3.88) and oral corticosteroid use (p = 0.015, PR = 1.93, 95% CI: 1.14–3.29). The duration of chronic diseases also increased the fungal infection rate, as seen in diabetes (p = 0.022, PR = 1.03, 95% CI: 1.01–1.06), kidney failure (p < 0.001, PR = 1.09, 95% CI: 1.05–1.12), corticosteroid use (p < 0.001, PR = 1.11, 95% CI: 1.06–1.17), and prolonged hospital stays (p < 0.001, PR = 1.02, 95% CI: 1.01–1.02). Subclinical factors related to fungal infection rates included turbid urine (p < 0.001, PR = 76.93, 95% CI: 10.55–560.75) and the presence of white blood cells in urine (p = 0.046, PR = 4.31, 95% CI: 1.03–18.09). Conclusion: This study revealed that fungal infections in elderly patients are often associated with underlying conditions, such as kidney failure, corticosteroid usage, prolonged chronic disease duration, or extended hospital stays. The outcome of paraclinical tests such as turbid urine or white blood cells in urine were also associated with fungal infections in elderly patients.
Keywords: factors related to fungal infections; urinary tract infections; elderly patients; Candida spp.; Tra Vinh General Hospital